ANALISIS IMPLEMENTASI SMM ISO 9001:2008 TERHADAP SERVICE PERFORMANCE PADA SMK PANCA BHAKTI BANJARNEGARA - , Sarastiana ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Service performance can be measured by the level of services received in the form of student satisfaction on the perceived service. This study was conducted to analyze the students' perceptions of the service performance of teachers, staff, curriculum, facilities and infrastructure impacts of the implementation of ISO 9001:2008 SMK Panca Bhakti Banjarnegara. The data was collected using a questionnaire instrument, and vocational students Panca Bhakti Banjarnegara respondents. Data were analyzed using the method of performance analysis interests. Results indicate that the performance of the services offered by the teacher obtained a score of 68.46%, employee service performance earned a score of 72.39%, obtained curricula service performance score of 71.61% and the performance of infrastructure obtained a score of 61.38%. After consultation with table service criteria (Table 3.11) the value of the service performance of teachers, staff, curriculum and infrastructure included in both categories.